2020
DOI: 10.15869/itobiad.783254
|View full text |Cite
|
Sign up to set email alerts
|

Üretim Yönetim Sistemlerindeki Kritik Başarı Faktörlerinin Rekabete Etkisi: Metal Sektöründe Bir Araştırma

Abstract: Bu makale, en az iki hakem tarafından incelenmiş ve intihal içermediği teyit edilmiştir. / This article has been reviewed by at least two referees and confirmed to include no plagiarism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…The results showed that although the benefits of the company from both the use of information systems and the adoption of sustainability practices were varied, they did not lead to a competitive advantage, at least not directly. Therefore, the results of this research are not completely aligned with the research conducted by Dao et al [11], Mastos et al [15], and Marinagi et al [12] and tend to agree with the views and conclusions of the authors who focus on the increased business performance as a key asset of using technologies to support sustainability practices [5][6][7][8][9][10].…”
Section: Conclusion and Limitationscontrasting
confidence: 53%
See 2 more Smart Citations
“…The results showed that although the benefits of the company from both the use of information systems and the adoption of sustainability practices were varied, they did not lead to a competitive advantage, at least not directly. Therefore, the results of this research are not completely aligned with the research conducted by Dao et al [11], Mastos et al [15], and Marinagi et al [12] and tend to agree with the views and conclusions of the authors who focus on the increased business performance as a key asset of using technologies to support sustainability practices [5][6][7][8][9][10].…”
Section: Conclusion and Limitationscontrasting
confidence: 53%
“…The study of the literature revealed that only a limited number of previous studies examined the relationship between information systems, sustainability practices, and competitive advantage [11][12][13][14][15]. It also revealed that many researchers put emphasis on the attainment of business performance [5][6][7][8][9][10] without examining whether it could also lead to competitive advantage. Furthermore, the review of the literature enabled us to study the theoretical approaches used in the relevant studies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation